THE HUMAN ADVANTAGE : THE FUTURE OF AMERICAN WORK IN AN AGE OF SMART MACHINES - Richards, Jay Wesley, 1967-
Summary: Bestselling author and economist Jay W. Richards makes the definitive case for how the free enterprise and virtue can save the American Dream in an age of A.I. and mass disruption.--Inside jacket flap